Arab–Islamic Civilisational Presence in West Africa: A Summary - BOUTERA, Ali (Journal of Ecohumanism, 2026)
This article addresses the subject of the Arab–Islamic civilisational presence in West Africa, noting that the existing relations between the northern and western parts of the African continent and the civilisational communication between them led to the emergence of the Islamic religion among the tribes of West Africa, particularly in the lands of the “Hausa”. With this civilisational expansion, the Arabic language, the language of the Qur’an, attained an elevated status and acquired significant importance despite the multiplicity of African dialects, beginning from the first Hijri century. This Islamic expansion coincided with commercial activity, and Muslim merchants were the first missionaries. Sultans from the Yusi and Wangara communities, from the fourteenth to the beginning of the nineteenth century CE, also played an important role in disseminating Islamic teachings. The Islamic Caliphate (al-Maktaba) emerged and endured for approximately a century (1804–1903), encompassing northern Nigeria, parts of southern Nigeria, and the present-day republics of Niger and Cameroon. This development protected the Muslims of the region from British ecclesiastical Christian missionary activity. The Arabic language advanced and became the language of composition among the peoples of West Africa (Western Sudan), and Arabic vocabulary entered the African dialects as loanwords. Thus, Swahili society became a community influenced by Islamic customs and principles. Swahili literature, written in the language of these peoples, emerged, drawing on Arab–Islamic literature and initially composed of Arabic, before being expressed in local languages. The emergence of written Yusi literature was the product of the intellectual revolution that accompanied the jihad movement in the lands of the Hausa and the establishment of the Maktaba Caliphate. The flourishing of scholarly activity had among its pioneers Shaykh Muḥammad ibn ʿAbd al-Karīm al-Maghīlī al-Tilimsānī in the late fifteenth century, as the Yusa lands were greatly influenced by him. At the beginning of the sixteenth century, small schools for local scholars appeared; they flourished and developed into centers of learning that attracted students from Africa. These emigrants were the spark from which the movement of thought and literature ignited and developed, culminating in the intellectual revolution that accompanied the idea of jihad. The city of Timbuktu was among the foremost and most important centers of scholarly and civilisational radiance.